Zopherobatrus gen. n. (Coleoptera: Staphylinidae: Pselaphinae), a new troglobitic batrisine from southwestern China - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2015)
A new genus and new species of the pselaphine tribe Batrisini, Zopherobatrus tianmingyii Yin & Li gen. et sp. n., is described based on material collected from a cave in Guizhou, southwestern China. The new taxon exhibits a typical suite of morphological adaptations to life in caves, and represents a third genus of the cave-inhabiting Pselaphinae in China.